2022
DOI: 10.1039/d2tc00965j
|View full text |Cite
|
Sign up to set email alerts
|

NiCo@NPC@CF nanocomposites derived from NiCo-MOF/cotton for high-performance electromagnetic wave absorption

Abstract: A cotton-based biomass material precursor was used to build lightweight, green, low-cost and high performance electromagnetic (EM) wave absorption materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…In order to analyze the source of dielectric loss in detail, the modified Debye relaxation model is fitted by the least square method. 31,35 The contribution of conduction loss and polarization loss calculated based on the parallel/series circuit model of resistor and capacitor, supplemented by the nonlinear fitting of the least square method is quantified in Fig. 5d–f.…”
Section: Resultsmentioning
confidence: 99%
“…In order to analyze the source of dielectric loss in detail, the modified Debye relaxation model is fitted by the least square method. 31,35 The contribution of conduction loss and polarization loss calculated based on the parallel/series circuit model of resistor and capacitor, supplemented by the nonlinear fitting of the least square method is quantified in Fig. 5d–f.…”
Section: Resultsmentioning
confidence: 99%
“…According to the classical electromagnetism theory, 55 EMW reflection is caused by the difference in wave impedance between air and materials, which means that higher electrical conductivity leads to a greater difference in wave impedance and stronger reflections. Moreover, on the basis of free electron theory, 56 ε ′′ = 1/2 ρε 0 π ƒ ( ρ is the resistivity, ε 0 stands for the free space dielectric constant), the electrical conductivity is proportional to ε ′′, so a high conductivity generates a large ε ′′, which can enhance the conduction loss. Several fluctuation peaks of ε ′ and ε ′′ curves can be observed at medium and high frequencies, which result from multiple interface polarizations and dipolar polarizations.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have found that composite absorbers are recognized as an effective method to overcome the weak EMWA capacity of single-component materials, the reasonable selection and combination of reinforcement and substrate matrix plays a vital role in the improvement of wave absorption performance. , 1D composite absorbers are commonly classified into three groups by their matrix materials: ceramic matrix, polymer matrix, and metal matrix composites . First, ceramic matrix composites are materials in which one or more distinct ceramic phases are intentionally added, which can enhance the wear resistance and thermal/chemical stability of EMWA materials.…”
Section: Electromagnetic Absorption Theorymentioning
confidence: 99%